Comparative analysis of anxiety assessment methods in athletes - H. Wardi; Y. A. Statsenko; I. A. Charykova; D. N. Tsvirko; I. M. Lyatina; A. A. Chumakova; A. S. Kulagin (National Electronic Information Consortium (NEICON), 2020)
Objective: to identify the most effective method for anxiety assessment in athletes. Materials and methods: the selective criteria were formulated and comparative analysis of 9 most commonly used methods of assessing the level of anxiety was made. 79 athletes of combat sports were tested (34 men, 45 women) in the preparative period of training with Lusher's color test and the integrative anxiety test by A.P. Bizyuk, L.I. Wasserman, B.V. Iovlev. Results: among nine methods most frequently mentioned in the literature, Lusher's color test with the calculation of diagnostic coefficients and the integrative anxiety test by A.P. Bizyuk, L.I. Wasserman, B.V. Iovlev were most consistent with the stated criteria. There were significant correlations between the calculated indices of Luscher's color test, which have physiological explanation: the correlation between the vegetative coefficient and the total deviation from the autogenic norm, mental working capacity, situational anxiety, and between total deviation from the autogenic norm and mental performance, sex (increase in the deviation from the autologous norm corresponds to a decrease in mental performance, an increase in the level of anxiety, parasympathetic tone, and need for rest and energy accumulation). The athletes have the low level of situational anxiety and an average level of personal anxiety if compared with average population values. Conclusions: the findings complement the results of other researchers who also confirmed the validity of use of color test and integrative anxiety test in professional sports to identify the threatening breakdown of mental adaptation and psycho-correction work among athletes.